The evolution of social behaviour in vervet monkeys: an experimental approach - (:unkn) unknown (My University, 2025)
Humans are highly social animals. In particular our ability to tolerate and even to cooperate with unrelated individuals appears to be unmatched by other species. A very influential hypothesis links our advanced cognitive abilities to the complexity of our social environment. More generally, it appears that brain size evolution in vertebrates is linked to a species' social complexity. In social species, an individual's main challenge for successful survival and reproduction is competition with fellow group members over access to limited resources like food and mates. At the same time, group members can be important alliance partners against predators and neighbouring groups. Cooperation and conflict are thus the two opposing forces that affect virtually any decision of individuals living in a group, selecting for increased cognitive abilities so that individuals can cope with the complexity of decision making in this dynamic social world. Our Sinergia project aims at testing links between ecology, social organisation, and social intelligence in a population of wild vervet monkeys in South Africa. Two key elements make our project different from previous research. First, we aim at large sample sizes (10 monkey groups) in order to be able to draw general conclusions. Second, we will conduct experiments under natural conditions rather than in the laboratory. Very well designed laboratory experiments on cognitive abilities exist, yet it is difficult to predict the extent to which these mechanisms are used under natural conditions. Sub-project A focuses on the monkeys' ability to show flexible social behaviour adapted to particularities of a situation. We will test what animals know about the relationships between other group members, and in how far they can exploit that knowledge to their advantage. Sub-project B investigates the animals' ability to engage in collective action in between-group conflict. We will investigate the role of genetic relatedness and of contextual factors on the decision to participate, and we will determine the consequences of success in between-group conflict on variables that are linked to reproductive success, like access to food. Sub-project C tests what mechanisms vervet monkeys use for social learning as well as under which conditions, and how innovations spread in the population. All three sub-projects will collaborate in the collection of basic information on home ranges, activity patterns, social behaviours, diet and food tree distribution, and the genetic structure of groups. The combined effort will constitute a world leading project expected to yield unique, novel insights into the social intelligence of wild primates.
Keywords: cognition; social learning; cooperation; Machiavellian intelligence; evolution; vervet monkeys; field experiments; vervet monkey; Chlorocebus aethiops; social behaviour; animal cognition; social brain hypothesis; between-group competition; kin selection; tradition